StoryFind : the handbook for finding and telling your nonprofit's most impactful stories - Sukraw, Kristin (Page Two, 2023)
"Within every nonprofit are incredible stories waiting to be shared. How do you raise awareness and boost fundraising efforts for your nonprofit's mission and important work? You tell story after story of impact and hope. Drawing on her years of experience as a therapist and owner of the production company StoryFind Films, author Kristin Sukraw shares the exact method her award-winning team uses to help organizations find and tell stories that deeply connect with audiences--and inspire donors to act. Time and time again, Sukraw has witnessed the power of storytelling when it comes to raising awareness for both nonprofits and purpose-driven for-profit organizations. A purposefully told story--whether in writing, audio or video--has the power to create a human connection, communicating your nonprofit's mission in a memorable way. Inside you'll get the five-step StoryFind Process, a template for creating a Master Plan, a roadmap for finding storytellers, tools for organizing a story, masterful interview techniques and basic editing methodology, all guiding you to share the experiences that can change lives."--